2016
DOI: 10.1007/s00520-016-3285-0
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and coping predict post-traumatic stress in caregivers of patients with head and neck cancer

Abstract: This preliminary study suggests that caregivers who have perceptions of low benefits from treatment and many patient symptoms, and those using avoidant coping strategies, are at increased risk of experiencing symptoms of PTSD. Psychological interventions that target illness perceptions and coping may help to reduce the prevalence of PTSD in caregivers of patients with HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…It is striking that there was no significant effect of cancer stage, site or treatment. This is in agreement with previous findings [35,21] and emphasises that PTSS experienced by cancer survivors may not consequently be connected to the severity of cancer or to sociodemographic factors. Contrary to previous findings, time since treatment was not associated with reduced PTSS [17,39] .…”
Section: Clinical Correlates Of Ptss and Ptsdsupporting
confidence: 93%
See 2 more Smart Citations
“…It is striking that there was no significant effect of cancer stage, site or treatment. This is in agreement with previous findings [35,21] and emphasises that PTSS experienced by cancer survivors may not consequently be connected to the severity of cancer or to sociodemographic factors. Contrary to previous findings, time since treatment was not associated with reduced PTSS [17,39] .…”
Section: Clinical Correlates Of Ptss and Ptsdsupporting
confidence: 93%
“…These results are not in line with the findings of Posluszny et al (2015) who reported significantly higher levels of PTSD in partners than in patients. Nevertheless, Richardson's findings suggested a similar prevalence rate between HNC patients and their caregivers [21,20]. Further research employing greater sample sizes is needed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cancer and its treatment causes many problems for patients (Otaghi, Hasanvand, Mozafari, & Khorshidi, 2019) and caregivers (Sisk, Kang, Goldstein, DuBois, & Mack, 2019) including psychological problems (Aziza, Wang, & Huang, 2019; Günay & Özkan, 2019). The psychological problems for these patients and their caregivers include care burden, depression, anxiety, and stress (DAS) (Jansen et al, 2018; Jasemi, Aazami, & Zabihi, 2016) and posttraumatic stress disorder (PTSD; Jia, Li, Chen, & Cao, 2015; Richardson, Morton, & Broadbent, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty related to disease and the family strain have been related to PTSD symptoms in a study on 333 caregivers of hematopoietic cell transplant recipients [52]. Richardson et al [53] found that in 78 caregivers of patients with head and neck cancer, having perceptions of low benefits from treatment and the presence of many patient symptoms, increased the risk of experiencing symptoms of PTSD in caregivers. Another study on 214 adult children caregivers of cancer patients highlighted that the perception of higher patient dependency was associated to higher PTSD symptoms [54].…”
Section: Risk Factors For Ptsdmentioning
confidence: 99%